Three's a crowd: Stella's pregnancy and the arrival of an "other" in A Streetcar Named Desire. (16th August 2019) - Jacobs, Daniel
Abstract: This paper explores the difficulties that may arise for some men when their wives become pregnant. The advent of a child may threaten the intense marital dyadic relationship on which a man may depend. The author explores how this particular threat to a husband's sense of security is manifest dramatically in Tennessee Williams's A Streetcar Named Desire. In this reading of the play, Stella's pregnancy and Stanley ' s feelings about it lie at the heart of the drama.